Means of state regulation of economic activity in conditions of deregulation of the economy of Ukraine - Кочин, Володимир Володимирович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
In the article the methods of state regulation of economic activity in terms of deregulation are reviewed. It is suggested to consider regulatory measures under the mechanism of economic and legal regulation of social relations and the introduction of systematic method of reforming economic relations within deregulation. The author states in the article that it is necessary to establish the place of the state in economic relations because of its ability to regulate economic activity in a market economy. It should focus on the economic principles of public administration, as well as the limits of the free market to create the appropriate economic and legal mechanisms of legal regulation of economic activity. Thus, the purpose of this work is to establish a means of state regulation of economic activity in terms of deregulation and Ukraine expressing proposals to improve the mechanism of legal regulation of economic activity. In this study we turn to the economic functions of the state, which aim to ensure proper formation, operation and development of the economy, protect existing ownership and creating conditions for their development. Commercial Code of Ukraine stipulates the main directions and forms of state involvement in economic activity. Thus, the principle is that the state, state authorities are not business entities, although they may have economic competence (ch. 1, 3 Art. 8 of the Commercial Code of Ukraine). To perform the economic function of the state various means and mechanisms of regulation of economic activity are used, the main of which are specified ch. 2, Art. 12 of the Commercial Code of Ukraine. The economic function of the state is appropriately adjusted to the economic policy which is based on the selected economic system. It should be noted that the regulatory consolidation course on the economic system provided for by the Association Agreement between Ukraine and the EU. The purpose of deregulation is to increase entrepreneurial activity, including through attracting foreign investment and reducing public “burden” on business by reducing the number of taxes and regulations. However, one should pay attention to the existing regulations of economic activities and determine their feasibility. We believe that these means of government regulation, as instruments of economic policy can be distinguished according to the stage mechanism of legal regulation, since they may be relevant in order adequately to the possibility entity to enter certain relations. We consider it appropriate to express views on the application by means of regulation of economic activity. First, you must determine the appropriate means of state regulation that would allow the entity enter the relevant market. Secondly, implementing provisions of the Association Agreement Ukraine and the EU will gradually introduction of EU standards, which according to experts is rather positive step. Thirdly, should “redistribute” government regulation and market self-regulation, which will be self-regulatory organizations in the application of the regulation of prices and tariffs, providing grants and subsidies and so on. Deregulation of the economy provides for reduction of state control over implementation of economic activities by introducing market. The state thus can regulate the existence of general principles of the market (stock, banking, insurance market etc.) through the formation of requirements status attributes of subjects and objects of technical regulation relations.